ANALISIS GAYA KEPEMIMPINAN DAN PENGARUHNYA TERHADAP KEPERCAYAAN KARYAWAN PT XYZ - Dingot Hamonangan Sitanggang (POLITEKNIK LP3I JAKARTA, 2020)
The purpose of this research is to obtain empirical data, facts, and valid and reliable information about the influence of the Leadership Style and its influence on the trust of the employees of PT. XYZ. This study uses an associative quantitative approach and regression techniques. The population in this study were all employees of PT. XYZ numbered 228 people. The sampling method using simple random sampling, for all employees who are still actively working in 2019, amounted to 228 people. Samples were taken with the Slovin formula so that the total sample of 145 people. Research data in the net through questionnaires. This study uses item analysis for both variables. The results of the study concluded, there is a positive direct effect of leadership style on employee trust. This finding means that if you want to increase employee confidence in the organization, it can be done through changing leadership styles.Keywords: Leadership Style, Trust, Millennial Generation